Direct job creation revisited: Is it effective for welfare recipients and does it matter whether participants receive a wage? - Joachim Wolff; Katrin Hohmeyer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
Bringing welfare recipients into jobs is a major goal of German labour market policy since a reform of the year 2005. Direct job creation providing participants with tem-porary subsidized jobs mainly in the non-profit sector plays an important role for achieving this goal. There are three schemes that differ only with respect to a few features: traditional job creation schemes, One-Euro-Jobs and work opportunities subsidising contributory jobs. We study and compare the effectiveness of these three job creation schemes for welfare recipients starting their participation in these programmes in mid 2005. Looking at three similar schemes enables us to study the implications of different programme features for the effectiveness. One major differ-ence between the schemes is that traditional job creation schemes and work oppor-tunities as contributory jobs provide participants with regular earnings, whereas One-Euro-Job participants only receive their benefit and on top a small allowance to cover costs of working. Hence, participation in One-Euro-Jobs in contrast to the other two programmes should provide higher incentives to search for regular jobs during participation. We estimate participation effects on employment outcomes, earnings and welfare benefit levels with propensity score matching using rich administrative data. We find that the programmes are partly effective in moving welfare recipients to work and reducing their welfare benefit dependency. Moreover, our findings imply that the incentives to search for regular jobs are not much lower for participants in the two schemes offering regular wages than for the alternative One-Euro-Jobs. Next, we find the most beneficial impacts for participants in work oppor-tunities as contributory jobs which is the only scheme that can subsidize commercial jobs.
Keywords: C13; I38; J68; 330; Evaluation of active labour market policy; propensity score matching; pair wise matching; workfare; welfare benefit recipients; work incentives